Method for manufacturing spicules coated with diamonds and ingredients effective for improving skin

JP7638545B2Active Publication Date: 2025-03-04BN CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022560152
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-02-24
Filing Date
2022-08-19
Publication Date
2025-03-04
Estimated Expiration
2042-08-19

AI Technical Summary

Benefits of technology

【0020】 本発明の製造方法によると、優れたアミノ基改質程度を有するスピキュールを得ることができ、これによって経皮吸収が促進されることができる。また、本発明の製造方法によって製造されたスピキュールは、内孔にコラーゲンなどの親水性有効成分を多量に含むことができ、外部が微細ダイヤモンドでコーティングされ、前記優れた皮膚剥離及び皮膚再生効果を与え、また経皮吸収効果と相乗効果を起こし、皮膚内部までに深く浸透して機能性に優れた化粧料組成物の製造に用いられる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638545000010
    Figure 0007638545000010
  • Figure 0007638545000011
    Figure 0007638545000011
  • Figure 0007638545000012
    Figure 0007638545000012
Patent Text Reader

Abstract

The present invention relates to a method for producing spicules that can promote transdermal absorption of skin-improving active ingredients and fine diamonds, and the spicules produced thereby and a cosmetic composition containing the same. The spicule cosmetic composition produced by the present invention can have excellent transdermal penetration efficacy and can be used to produce a cosmetic composition with excellent functionality.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a needle-shaped structure for promoting percutaneous absorption, which can promote percutaneous absorption of an ingredient effective for improving skin, a needle-shaped structure produced by the method, and a cosmetic composition containing the same. [Background technology]

[0002] As appearance is recognized as one measure of health, interest in skin health has increased, and in the cosmetics industry, interest in environmentally friendly materials that are harmless to the human body and have functional effects on the skin is growing. In particular, synthetic surfactants, pigments, antioxidants, and chemical preservatives contained in cosmetics are known to dry out the skin and may induce rashes, inflammation, skin diseases, and even skin cancer, and there is a high demand for cosmetics that use natural substances as main ingredients instead of chemical ingredients that are harmful to the skin. In particular, research on naturally derived functional substances is attracting attention in the field of functional cosmetics, which focuses on the additional functional effects of cosmetics.

[0003] Among these natural substances, spicules (sponge bone fragments) are also known as sponges. Porifera are primitive marine organisms that lack muscles, nerves, or organs. There are more than 5,000 species of them, and they are found at any depth in the ocean. Spicules are needle-shaped tissues that exist in the bodies of invertebrates and perform the function of the skeleton, and are mainly composed of silica and calcium carbonate. The fibrous skeleton of sponges has the ability to absorb fluids through capillary action, and is therefore used in various fields, including medical applications. For example, sponge bone fragments contain antibiotics for the treatment of osteomyelitis, and are used for the treatment and prevention of diseases.

[0004] Since the above-mentioned sponge-derived spicules have a needle-like structure, they are particularly suitable for delivering active ingredients to the transdermal layer of the skin, and attempts have been made to use them in cosmetic compositions.

[0005] Prior patent documents of the present invention include Korean Patent Registration No. 10-2074214 (Patent Document 1).

[0006] Against this background, the present inventor has completed and provided an invention that provides an optimal manufacturing method for using the above-mentioned needle-shaped structures derived from marine sponges in cosmetic compositions, which includes a fine diamond coating and an amino group modification step. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Republic of Korea Patent No. 10-2074214 Summary of the Invention [Problem to be solved by the invention]

[0008] The technical problem that the present invention aims to achieve is to provide a method for producing spicules that are excellent in transdermal absorption, more specifically, to provide a method for producing a needle-shaped structure that contains a skin-improving active ingredient and is coated with diamond, and the needle-shaped structure produced thereby.

[0009] Another object of the present invention is to provide a cosmetic composition containing spicules produced by the above method.

[0010] However, the technical problem that the present invention aims to achieve is not limited to the problems mentioned above, and other problems not mentioned will be clearly understood by a person of ordinary skill in the art from the following description. [Means for solving the problem]

[0011] In order to solve the above problems, the present invention provides a method for producing a spicule coated with a skin-improving active ingredient and diamond, comprising the steps of: (a) cleaning the spicules; (b) encapsulating a first active ingredient within the pores of the washed spicules; (c) coating the exterior of the spicules having the first active ingredient encapsulated in the inner pores with silica; (d) reacting the silica-coated spicules with aminosilane and lysine to coat them with amino groups; and (e) coating the amino-coated silica with a second active ingredient and diamond.

[0012] According to one embodiment, the aminosilane in step (d) can be 3-aminopropyltrimethoxysilane.

[0013] According to one aspect, the lysine in step (d) can be poly-L-lysine.

[0014] According to one aspect, the mixing ratio of aminosilane and lysine in step (d) may be 1:1 to 500:1.

[0015] According to one aspect, the diamond in step (e) may be one or more selected from the group consisting of microdiamond, nanodiamond, and colloidal diamond.

[0016] According to one aspect, the first active ingredient and the second active ingredient are each at least one selected from the group consisting of collagen, fish collagen, nano-collagen, low molecular weight collagen, vegetable collagen, collagen peptide, amino acid, tripeptide, tetrapeptide and water-soluble vitamin, and the first active ingredient and the second active ingredient may be the same or different ingredients.

[0017] According to another embodiment of the present invention, there is provided a cosmetic composition comprising the spicules produced by the above method.

[0018] On the one hand, the cosmetic composition may have a skin exfoliating effect.

[0019] On the one hand, the cosmetic composition may have an effect of improving wrinkles. Effect of the Invention

[0020] According to the manufacturing method of the present invention, spicules having an excellent degree of amino group modification can be obtained, which can promote percutaneous absorption. In addition, the spicules manufactured by the manufacturing method of the present invention can contain a large amount of hydrophilic active ingredients such as collagen in the inner pores, and the outside is coated with fine diamond, which gives the excellent skin peeling and skin regeneration effects, and also has a synergistic effect with the percutaneous absorption effect, so that it can be used to manufacture a cosmetic composition with excellent functionality by penetrating deep into the skin.

[0021] The effects of the present invention are not limited to the effects described above, but should be understood to include all effects that can be inferred from the configuration of the invention described in the detailed description of the present invention or the claims. [Brief description of the drawings]

[0022] [Figure 1] 1 is a schematic diagram showing a method for producing a needle-shaped structure according to the present invention. [Diagram 2] The degree of fluorescence coloring of fluorescent collagen varies depending on whether it is enclosed in the pores. [Diagram 3] The graph shows the degree of fluorescent color development for examples produced using different production methods. [Figure 4] 1 shows the degree of skin absorption of the cosmetic composition prepared containing the needle-shaped structure of the above Preparation Example. [Diagram 5] The skin peeling effect of a cosmetic composition containing a needle-shaped structure produced by the production method of the present invention was evaluated. [Figure 6]The cosmetic composition containing the needle-shaped structures produced by the production method of the present invention was evaluated for its effect of improving wrinkles around the eyes. [Figure 7] 1 is a graph showing the cell survival effect of a cosmetic composition containing the modified spicules of the present invention. [Figure 8] 1 is a graph showing the collagen synthesis effect of a cosmetic composition containing the modified spicules of the present invention in NHDF cells. [Figure 9] 1 is a photograph showing the effect of a cosmetic composition containing the modified spicules of the present invention on collagen fiber production in NHDF cells (green: collagen fibers, scale bar: 20 μm). [Figure 10] 1 is a graph showing the skin absorbency of cosmetic composition 3 containing the modified spicules of the present invention and cosmetic composition 1 containing general spicules. [Figure 11] 1 is a graph comparing the skin absorbency of cosmetic composition 3 containing modified spicules of the present invention and cosmetic composition 1 containing non-diamond coated spicules. [Figure 12] 1 is a graph showing the skin absorption depth of cosmetic composition 3 containing modified spicules of the present invention and cosmetic composition 1 containing spicules not coated with diamond. [Figure 13] 1 is a graph comparing the skin absorption depth of cosmetic composition 3 containing modified spicules of the present invention and cosmetic composition 1 containing non-diamond coated spicules. [Figure 14] 1 is a graph showing the skin absorption rate of cosmetic composition 3 containing modified spicules of the present invention and cosmetic composition 1 containing spicules not coated with diamond. [Figure 15] 1 is a graph comparing the skin absorption rate of cosmetic composition 3 containing modified spicules of the present invention and cosmetic composition 1 containing spicules not coated with diamond. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] According to one embodiment of the present invention, there is provided a method for producing a spicule, comprising the steps of: (a) cleaning the spicules; (b) encapsulating a first active ingredient within the pores of the washed spicules; (c) coating the exterior of the spicules having the first active ingredient encapsulated in the inner pores with silica; (d) reacting the silica-coated spicules with aminosilane and lysine to coat them with amino groups; and (e) coating the amino-coated silica with a second active ingredient and diamond; The present invention provides a method for producing spicules containing diamond and an ingredient effective for improving skin, comprising:

[0024] The terms "spicule", "needle-shaped body", or "needle-shaped structure" used herein refer to a structure having a fine structure in a needle shape, and the terms "spicule", "needle-shaped body", and "needle-shaped structure" can be used interchangeably herein. Preferably, the needle-shaped structure is derived from a marine sponge, and more preferably, the marine sponge is Spongilla lacustris. The bone fragments or bone needles of the marine sponge are used as the spicules in the present invention.

[0025] The spicules may be composed of calcium or silica, and may have a porous interior. The spicules may have an I-type structure, a Y-type structure, or an X-type structure. Specifically, the spicules may have a Monoaxon pattern, a Triaxon pattern, a Tetraxon pattern, or a Polyaxon pattern. The Triaxon pattern may be a Triactine pattern or a Hexactine pattern. The "Monoaxon" refers to a spicule having a needle-like shape with a pointed tip. Preferably, the spicules may have an I-type structure and a Monoaxon pattern.

[0026] The spicules may be obtained from a marine sponge and further purified.

[0027] The coated spicules may contain ingredients effective for improving skin inside. The spicules of the present invention are characterized in that they contain pure spicules with all natural impurities removed from inside. Therefore, the spicules may contain ingredients effective for improving skin in their internal porous structure.

[0028] The ingredient effective for improving skin may be a cosmetically effective ingredient, and may include ingredients for improving or enhancing skin function, ingredients for preventing deterioration of skin condition, ingredients for complementing skin shortcomings or highlighting skin advantages, etc. Non-limiting examples of the active ingredient include collagen, fish collagen, nano-collagen, low molecular weight collagen, plant collagen, collagen peptides, amino acids, tripeptides, tetrapeptides, and water-soluble vitamins.

[0029] The term "collagen" as used herein means a semi-crystalline aggregate of collagen molecules. Specifically, collagen is a major protein forming the extracellular matrix formed of a triple helix composed of amino acids, and is the main component of connective tissue. The collagen may be collagen derived from the human body. The collagen derived from the human body may be fibrillar collagen or non-fibrillar collagen.

[0030] The spicules may be modified by surface coating. Specifically, the surface may be coated with diamond. The diamond-coated spicules may improve the dermal absorption of active ingredients compared to non-diamond-coated spicules, and thus the dermal absorption rate of active ingredients may be increased.

[0031] The diamond used for the coating can be in the form of diamond powder or liquid. The diamond used here can be one or more selected from the group consisting of microdiamond, nanodiamond, and colloidal diamond. Specifically, the diamond can be nanodiamond.

[0032] The spicules may also include a silica coating on the surface.

[0033] The silica coating means that it is coated with a material containing silicon dioxide.

[0034] A specific example of the silica is tetraethylorthosilicate or siloxane polymer. The silica coating can improve the binding performance with the active ingredient by modifying the surface of the needle-shaped body.

[0035] The spicules may include an amino group coating on the surface thereof. The amino group coating refers to a coating layer of a substance containing an amino group. The amino group coating refers to coating the spicules with a substance or amino acid that contains an amino group at its terminal.

[0036] The amino group coating can be an aminosilane coating and / or a lysine coating.

[0037] The term "amino silane" used in this specification refers to an N-silyl compound in which hydrogen is replaced by an amino group, and is represented by the chemical formula SiH4 and is also called amino silane. The amino silane is a type of silane coupling agent and can form a hydrophilic coating layer.

[0038] The aminosilane can be N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-triethoxysilyl-N-(1,3 dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, 3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, hydrolysates thereof, derivatives thereof, or combinations thereof.

[0039] The term "lysine" as used herein is a type of amino acid and may include polylysine, which is a homogeneous amino acid polymer of lysine. The lysine may be poly-L-lysine, poly-D-lysine, or a combination thereof.

[0040] In one embodiment, the aminosilane can be 3-aminopropyltrimethoxysilane, and the lysine can be poly-L-lysine.

[0041] The washing in step (a) is for removing organic impurities present in the inner pores of the needle-shaped mold body, and is carried out using purified water and a basic or acidic solution. Preferably, the washing of the needle-shaped mold body can be carried out by washing the needle-shaped mold body one or more times with purified water, followed by treatment with an acidic solution such as sulfuric acid, hydrochloric acid, hydrofluoric acid, or hydrogen peroxide, or a basic solution such as sodium hydroxide or potassium hydroxide.

[0042] According to one aspect, the encapsulation of the inner pores in step (b) is performed by ultra-high pressure treatment in which a pressure of 50-300 MPa is applied for 1-10 minutes, and the first active ingredient is preferably a hydrophilic active ingredient, non-limiting examples of which include amino acids, tripeptides, tetrapeptides, water-soluble vitamins, etc. Under these conditions, the first active ingredient can be excellently encapsulated in the inner pores.

[0043] The silica coating in step (c) is preferably carried out by reacting with tetraethylorthosilicate. The silica coating process can improve the binding performance with the active ingredient by modifying the surface of the needle-shaped body. The coating reaction is preferably carried out at 25-50°C for 30 minutes to 2 hours, and may include ultra-high pressure treatment in which a pressure of 50-300 MPa is applied for 1-10 minutes. Under the above conditions, silica coating is performed to the best extent.

[0044] According to one aspect, the aminosilane in step (d) can be 3-aminopropyltrimethoxysilane, and the lysine in step (d) can be poly-L-lysine.

[0045] On the one hand, the aminosilane in step (d) may be included in a higher weight amount than the lysine. Specifically, the aminosilane and lysine may have a weight ratio of 1:1 to 1000:1. Preferably, the weight ratio is 500:1. The aminosilane reacts with the spicules in the form of a mixed solution with lysine, and the mixed ratio is preferably 0.01 to 5 parts by weight per 1 part by weight of the spicules. If the ratio is outside the above range, there may be a problem that the efficiency of the inclusion of diamond and the active ingredient in the spicules decreases.

[0046] As verified in Examples 5 and 6 below, when the mixed weight ratio of aminosilane and lysine is 500:1, it shows the best fluorescent collagen encapsulation ability and skin absorption degree, and in particular shows a better transdermal absorption rate.

[0047] The amino group coating in step (d) is a step for modifying the surface of the needle-shaped body, and is preferably carried out after silica coating. The reaction for coating the amino group is preferably carried out at 25 to 50°C for 30 minutes to 2 hours, and an ultra-high pressure treatment is carried out by applying a pressure of 50 to 300 MPa for 1 to 10 minutes. The modification to amino groups is excellent under the reaction conditions.

[0048] According to one aspect, the diamond in step (e) may be one or more selected from the group consisting of microdiamond, nanodiamond, and colloidal diamond.

[0049] According to one aspect, the first active ingredient and the second active ingredient are each at least one selected from the group consisting of collagen, fish collagen, nano-collagen, low molecular weight collagen, plant collagen, collagen peptides, amino acids, tripeptides, tetrapeptides, and water-soluble vitamins, and the first active ingredient and the second active ingredient may be the same or different ingredients.

[0050] According to another embodiment of the present invention, there is provided a cosmetic composition comprising the spicules prepared by the above method. The content of the spicules is not particularly limited, but may be preferably 0.1 to 5 parts by weight based on 100 parts by weight of the cosmetic composition. The composition can show the best percutaneous absorption rate and skin peeling effect.

[0051] The skin-improving active ingredient contained in the cosmetic composition may include an ingredient for improving or enhancing skin function, an ingredient for suppressing deterioration of skin condition, or an ingredient for complementing skin shortcomings or highlighting advantages. The content of the active ingredient is not particularly limited, but may be preferably 0.05 to 1 part by weight based on 100 parts by weight of the cosmetic composition. In addition to the active ingredient, the cosmetic composition according to the present invention may contain various ingredients contained in ordinary cosmetic compositions. For example, all substances commonly used in mask sheets, such as dispersants, thickeners, surfactants, preservatives, moisturizers, stabilizers, solubilizers, pigments, and fragrances, may be included.

[0052] On the one hand, the cosmetic composition may have a skin exfoliating effect.

[0053] On the one hand, the cosmetic composition may have a wrinkle improving effect.

[0054] The cosmetic composition according to an embodiment of the present invention may further include purified water, an antioxidant, a stabilizer, a pigment, or a fragrance, which are commonly used in the field of cosmetic compositions.

[0055] In addition, the cosmetic composition according to an embodiment of the present invention may be prepared in a conventional dosage form. Specifically, it may be prepared in a dosage form including skin lotion, skin soap, skin toner, astringent, lotion, milk lotion, moisture lotion, nutrient lotion, massage cream, nutrient cream, moisture cream, eye cream, hand cream, foundation, essence, nutrient essence, eye essence, pack, soap, cleansing foam, cleansing lotion, cleansing cream, body lotion, body cream, body cleanser, suspension, gel, powder, paste, mask pack or sheet, or aerosol composition. It may also be applied in various phases suitable for providing moisture to the skin, such as gel, cream, paste, solid phase, etc., and specifically, it may be a gel cream with a particle feel such as sherbet or slush. The composition in such a dosage form may be prepared by a conventional method in the art.

[0056] In one embodiment, the composition may further include one or more selected from the group consisting of oils, purified water, emulsifiers, dispersants, colorants, flavorings, UV blocking agents, sweeteners, vitamins, and sequestering agents. Also, in one embodiment, the composition may further include 0.1% to 3.0% by weight of a preservative.

[0057] The amount of the additional components such as the oils can be easily selected by those skilled in the art within a range that does not impair the object and effect of the present invention.

[0058] The cosmetic composition according to one embodiment may preferably be in the form of a cream. For example, when the cosmetic composition has a cream form, it can contain the coated spicules of the present invention evenly, and is effective in moisturizing the skin while allowing the spicules to penetrate the skin.

[0059] The cosmetic composition according to one embodiment may further comprise any conventional cosmetic ingredient selected from additional ingredients commonly used in cosmetics, such as dispersants, thickeners, pigments, fragrances, fillers, preservatives, antiseptics, neutralizing agents, UV blocking agents, sweeteners, vitamins, free radical scavenger, sequestering agents, and mixtures thereof. EXAMPLES

[0060] Hereinafter, the embodiments will be described in detail with reference to the attached drawings. However, various modifications may be made to the embodiments, and the scope of the patent application is not limited or restricted by such embodiments. It should be understood that all modifications, equivalents, or alternatives to the embodiments are included in the scope of the patent.

[0061] The terms used in the examples are merely used for the purpose of explanation and should not be construed as being limiting. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include" or "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and should be understood not to preclude the presence or additional possibility of one or more different features, numbers, steps, operations, components, parts, or combinations thereof.

[0062] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as commonly understood by a person of ordinary skill in the art to which the embodiments belong. Terms as defined in commonly used dictionaries should be interpreted as having a meaning consistent with the meaning they have in the context of the relevant art, and should not be interpreted as idealized and overly formal unless expressly defined in this application.

[0063] In addition, in the description with reference to the accompanying drawings, the same components are given the same reference numerals regardless of the drawing numerals, and the duplicated description thereof will be omitted. In describing the embodiments, if it is determined that a detailed description of related known technology may unnecessarily obscure the gist of the embodiments, the detailed description thereof will be omitted.

[0064] [Example 1. Acquiring spicules] Example 1-1. Cleaning of spicules The spicules have needle-shaped structures and are extracted from the Russian sponge Spongilla lacustris L. The spicules with internal holes are washed through the following process. 100g of the spicules were placed in 1,000ml of purified water to remove salt, and filtered through a 400 mesh polyethylene (PE) filter. The spicules remaining on the filter were washed twice with purified water. The spicules were then sterilized in 1,000ml of 70% ethanol, filtered through a 400 mesh polyethylene (PE) filter, and the spicules remaining on the filter were washed twice with purified water. The washed spicules were then placed in a dryer (Hanbaeksci) and dried at 50°C.

[0065] In order to remove impurities remaining in the dried spicules, the dried spicules were placed in 1,000 ml of 35% hydrogen peroxide (H2O2) (SAMCHUN CHEMICALS) and ultrasonically treated at 60°C for 1 hour at 300 W and 40 kHz using an ultrasonic cleaner (Sungdong Ultrasonics). After that, the spicules were filtered through a 400 mesh polyethylene (PE) filter, and the spicules remaining on the filter were washed with 500 ml of purified water, which was repeated three times. The washed spicules were then placed in a dryer and dried at 50°C to complete the washing of the spicules.

[0066] Example 1-2. Encapsulating the first active ingredient in the inner pores of the spicules 100 g of the washed spicules were added with 500 ml of 1N HCL (Sigma-Aldrich) and reacted for 1 hour, then 500 ml of 1N NaOH (Sigma-Aldrich) was added to neutralize them, and 1,000 ml of 10% sodium percarbonate was added and reacted for 1 hour to remove organic impurities from the inner pores.

[0067] 10 g of the mixture containing spicules and collagen, the first active ingredient, was placed in a vinyl bag and subjected to vacuum pressure reduction, followed by pressure treatment at a pressure of 150 MPa for 5 minutes using a high-pressure processor (Ilshin Autoclave, Suflux (registered trademark)). The mixture was then filtered through a 400 mesh polyethylene (PE) filter, and the spicules remaining on the filter were washed with 500 ml of purified water, which was repeated three times. The washed spicules were then placed in a dryer and dried at 50°C to complete the washing of the encapsulated spicules.

[0068] Test Example 1-3. Silica Coating The spicules obtained in Example 1-2 were reacted with a 1% tetraethylorthosilicate solution for 1 hour to coat the spicules with silica.

[0069] Test Example 1-4. Amino Group Coating 0.01 parts by weight of 3-aminopropyltrimethoxysilane, 0.01 parts by weight of poly-L-lysine (mixing ratio 1:1), and 98.98 parts by weight of water were added to 1 part by weight of silica-coated spicules obtained in Example 1-3, and reacted for 1 hour to coat the spicules with amino groups. The spicules were then washed with 500 ml of purified water, and this process was repeated three times. Then, 0.01% by weight of collagen (Sigma-Aldrich) bound with FITC (Fluorescein-5-isothiocyanate, Thermo Fisher Scientific) and nanodiamonds were added and reacted at room temperature for 1 hour.

[0070] Next, the prepared mixture was filtered through a 400 mesh polyethylene (PE) filter, and the diamond bonded structure remaining on the filter was washed with 500 ml of purified water, which was repeated three times.The washed diamond bonded structure was then placed in a dryer and dried at 50°C to obtain a needle-shaped structure in which collagen was contained in the inner pores and diamond and fluorescent collagen were bonded to the amino groups of the spicules.

[0071] [Example 2. Preparation of aminosilane to polylysine with a weight ratio of 10:1] The same preparation as in Example 1 was carried out, except for the composition of the solution used for amino group coating. 0.1 parts by weight of 3-aminopropyltrimethoxysilane, 0.01 parts by weight of poly-L-lysine (mixing ratio 10:1), and 98.89 parts by weight of water were added to 1 part by weight of spicules, and the mixture was reacted for 1 hour to coat the amino groups. All other reaction conditions were the same as in Example 1, except for the composition of the solution used for amino group coating.

[0072] [Example 3. Example of the production of aminosilane to polylysine with a weight ratio of 100:1] The same preparation as in Example 1 was carried out, except for the composition of the solution used for amino group coating. 1 part by weight of spicules was mixed with 1 part by weight of 3-aminopropyltrimethoxysilane, 0.01 part by weight of poly-L-lysine (mixing ratio 100:1), and 97.99 parts by weight of water, and reacted for 1 hour to coat the amino group. All other reaction conditions were the same as in Example 1, except for the composition of the solution used for amino group coating.

[0073] [Example 4. Production example of aminosilane to polylysine weight ratio of 500:1] The same preparation as in Example 1 was carried out, except for the composition of the solution used for amino group coating. 5 parts by weight of 3-aminopropyltrimethoxysilane, 0.01 parts by weight of poly-L-lysine (mixing ratio 500:1), and 93.99 parts by weight of water were added to 1 part by weight of spicules, and the mixture was reacted for 1 hour to coat the amino groups. All other reaction conditions were the same as in Example 1, except for the composition of the solution used for amino group coating.

[0074] Comparative Example 1 The spicules, which had not undergone the silica coating and amino group coating processes and had not been encapsulated in the first active ingredient in the spicules, were washed with 500 ml of purified water three times. Then, 0.01 wt% of collagen (Sigma-Aldrich) bound with FITC (Fluorescein-5-isothiocyanate, Thermo Fisher Scientific) and nanodiamonds were added and reacted at room temperature for 1 hour. Next, the mixture was filtered through a 400 mesh polyethylene (PE) filter, and the diamond bonded structure remaining on the filter was washed with 500 ml of purified water three times. Then, the washed diamond bonded structure was placed in a dryer and dried at 50°C to obtain a needle-shaped structure having diamond and collagen only on the outer surface of the spicule.

[0075] Comparative Example 2 Spicules coated with only silica were obtained through the steps of the above-mentioned Examples 1-1 to 1-3. The spicules were then washed with 500 ml of purified water three times. Then, 0.01% by weight of collagen (Sigma-Aldrich) bound with FITC, a fluorescent substance, and nanodiamonds were added and reacted at room temperature for 1 hour. The mixture was then filtered through a 400 mesh polyethylene (PE) filter, and the diamond-bonded structure remaining on the filter was washed with 500 ml of purified water three times. The washed diamond-bonded structure was then placed in a dryer and dried at 50°C to obtain a structure in which diamond and fluorescent collagen were bound to the amino group of the spicules. This needle-shaped structure was not coated with amino groups.

[0076] Comparative Example 3 0.01 parts by weight of 3-aminopropyltrimethoxysilane solution and 99.9 parts by weight of water were added to 1 part by weight of spicules coated with only silica obtained through the processes of Examples 1-1 to 1-3, and reacted for 1 hour to coat the amino group. Next, the process of washing the spicules with 500 ml of purified water was repeated three times. Then, collagen (Sigma-Aldrich) bound with FITC, a fluorescent material, and 0.01% by weight of nanodiamond were added and reacted at room temperature for 1 hour. Next, the prepared mixture was filtered through a 400 mesh polyethylene (PE) filter, and the diamond bonded structure remaining on the filter was washed with 500 ml of purified water three times. Then, the washed diamond bonded structure was put into a dryer and dried at 50°C to obtain a structure in which diamond and fluorescent collagen were bound to the amino group of the spicules. Poly-L-lysine was not used in the amino group coating of this needle-shaped structure.

[0077] The spicule manufacturing conditions of the comparative example and the example, and the fusion rate results of the diamond and collagen outside the spicule structure obtained as a result, are summarized in the following Table 1. The diamond-collagen fusion rate (%) was calculated as follows. Fusion rate (%) = (fluorescence value of collagen bound to spicules after diamond-collagen fusion) / (fluorescence value of total collagen used) × 100

[0078] [Table 1]

[0079] From Table 1 above, it can be seen that the fusion rate between diamond and collagen in the examples of the present invention is excellent.

[0080] Experimental example 1. Evaluation of pore inclusion For the evaluation of the inclusion of the inner pores, the spicules of Comparative Example 1, which do not undergo inclusion of the inner pores, and the spicules of Comparative Example 2, which undergo inclusion of the inner pores, were selected and evaluated. 5 mg of spicules and 1 mg of FITC were mixed in 0.2 ml of purified water to prepare a mixture, and 0.1 mg of spicules were taken from the mixture, placed on a slide glass, and observed with a fluorescent microscope (Nikon, Ts2-FL) using a GFP filter, and the results are shown in FIG. 2. As shown in FIG. 2, the spicules of Comparative Example 2, which undergo inclusion of the inner pores, showed superior fluorescence compared to the spicules of Comparative Example 1, which do not undergo inclusion of the inner pores. In other words, it was confirmed that the active ingredient could be impregnated inside the spicules through the inclusion of the inner pores of the spicules.

[0081] Experimental Example 2. Fluorescent collagen inclusion evaluation To evaluate the fluorescent collagen encapsulation ability of spicules, the spicules obtained in Comparative Examples 3 and 4 and Examples 1 to 4 were evaluated as follows. 5 mg of spicules was mixed with 0.2 ml of purified water to prepare a mixture, and then 0.1 mg of spicules was taken from the mixture, placed on a slide glass, and observed under a fluorescent microscope (Nikon, Ts2-FL) with a GFP filter, and the results are shown in Figure 3. As shown in Figure 3, it was confirmed that fluorescent collagen was encapsulated excellently in Example 4.

[0082] Experimental Example 3. Preparation of cosmetic composition and evaluation of its functionality 3-1. Production of cosmetic composition A cosmetic composition was prepared using the spicules of Comparative Example 2 and Examples 1 to 4 in Table 1 above. Specifically, 10.0 wt% glycerin (humectant), 3.0 wt% butylene glycol, 1.0 wt% sodium chloride, and 4.0 wt% hydrolyzed collagen were added to 59.675 wt% purified water, and stirred at 1,000 rpm for 10 minutes to prepare an aqueous phase solution. Then, in order to prepare an oily phase solution, 8.0 wt% caprylic / capric triglyceride (oil), 4.0 wt% diisostearyl malate (oil), 4.0 wt% cetyl pidi / pidi-10 / 1 dimethicone (emulsifier), and 3.0 wt% butylene glycol dicaprylate / dicaprate were mixed and dissolved by heating at 60°C, and the prepared aqueous phase solution was added and stirred at 1,000 rpm to prepare an aqueous phase solution. Then, 2 wt% of spicules (Comparative Examples 3, 4, and Examples 1 to 4) were further added to the cosmetic composition, and the mixture was stirred at 2,000 rpm for 5 minutes at 60°C. Finally, 0.025 wt% diamond powder, 1.0 wt% preservative, and 0.3 wt% fragrance were added, and the mixture was stirred at 3,000 rpm for 5 minutes at 50°C to prepare a cosmetic composition. Hereinafter, the cosmetic compositions obtained by blending the spicules of Comparative Examples 3 and 4 are referred to as Compositions 1 and 2, respectively, and the cosmetic composition obtained by blending the spicules of Example 4 is referred to as Composition 3, respectively.

[0083] 3-2. Evaluation of the degree of skin absorption of cosmetic compositions An experiment was conducted to confirm the degree of skin absorption (penetration) of compositions 1 to 3 obtained in 3-1. The compositions 1 to 3 were applied to pig skin (Franz Cell Membrane, FCM, APURES) and the tissue sections of the pig skin were observed under a fluorescent microscope (Nikon, Ts2-FL), and the results are shown in FIG. 4 and Table 2. The tissue sections were prepared by spreading and applying 0.25 g of the composition on pig skin (2 x 2 cm) four times at 10-minute intervals, leaving the tissue sections at room temperature for 24 hours, then fixing the tissue sections in 2 ml of 3.7% formaldehyde (Sigma-Aldrich) for 20 minutes, washing the tissue sections three times with 1XPBS, freezing the tissue sections in OCT (Optimal cutting temperature compound, Sakura Finetech) at -20°C, and cutting the tissue sections to a thickness of 15 μm using a cryostat microtome (Leica Biosystems).

[0084] [Table 2]

[0085] 4 and Table 2, it was confirmed that no fluorescence was observed in the epidermis and dermis layers of the skin for Compositions 1 and 2, whereas fluorescence was observed in the epidermis and dermis layers of the skin for Composition 3. This is because the fluorescent protein penetrated into the epidermis and dermis layers, proving that the cosmetic composition according to the present invention has excellent dermal absorption (penetration).

[0086] 3-3.Skin peeling evaluation In order to confirm the degree of skin keratin exfoliation of the cosmetic compositions of Composition 1 and Composition 3, the keratin exfoliation effect was measured on 15 adult men and women aged 20 to 40 years old, and the results are shown in Figure 5. Specifically, before applying the sample, the test subjects placed 10% by weight of dihydroxyacetone in a Hilltop chamber and applied it to the inside of the upper arm for 5 hours. After 24 hours, the color of the stained area was measured with a Chromameter (Minolta) and the difference in color before and after the sample application was measured. For two weeks, appropriate amounts of the cosmetic compositions of Composition 1 and Composition 3 were applied to the affected area twice a day, in the morning and afternoon. Thereafter, the degree of decolorization was measured with a Chromameter, and the time it took for the skin to return to its original color was measured. The keratin exfoliation rate was calculated using the following formula. Corneal peeling rate (%) = (Turnover time of blank - Turnover time when sample was applied) / (Turnover time of blank) * 100 Blank Turnover time: The time it takes for the stratum corneum in the untreated sample group to be replaced by new stratum corneum. Turnover time after sample application: The time it takes for the stratum corneum of the sample-treated group to be replaced by new stratum corneum.

[0087] As shown in FIG. 5, the group treated with Composition 3 showed an excellent keratin peeling rate.

[0088] 3-4. Evaluation of improvement of wrinkles around the eyes In order to confirm the effect of Composition 3 in preventing skin aging, the improvement of eye wrinkles was evaluated based on the standard operating guidelines (SOP) of the Cosmetic Clinical Research Support Center of Semyung University, and the results are shown in Figure 6. Specifically, 20 female test subjects aged 20 to 55 years (average age 42.9 years) took an appropriate amount of the cosmetic composition of Composition 3 and applied it to their eyes twice a day, in the morning and afternoon, for 4 weeks. Thereafter, to analyze eye wrinkles, the test subjects' eyes were imaged with Antera3D (Miravex, Ireland) under constant temperature and humidity conditions (22±2°C, RH40-60%) after 2 and 4 weeks, and the instrumental analysis values ​​were measured using the analysis program provided by the device (Antera3D software, Miravex, Ireland). The photographs on the left side of Figure 6 are photographs of the same area at 0 and 4 weeks, and the graph on the right side shows the reduction rate of eye wrinkles. It was confirmed that by using the cosmetic composition of Composition 3, wrinkles around the eyes were improved by 13.8% at 4 weeks compared to 0 weeks.

[0089] Experimental Example 4. Confirmation of in vitro collagen production effect of cosmetic composition 4-1. Experimental materials and preparation The in vitro collagen production effect was confirmed using the ivory cream-colored formulation of Composition 3.

[0090] Fetal bovine serum (FBS), r-Human Fibroblast Growth Factor-B (rhFGF-B), INSULIN, Gentamicin sulfate, and Amphotericin-(GA1000) Fibroblast Basal Medium (FBM) used in the cell experiments were purchased from Lonz (USA), and EZcytox was purchased from DAEILLAB SERVICE (Korea). In particular, for the intracellular collagen production measurement test, culture media were prepared with the cosmetic composition at final concentrations of 0.001%, 0.005%, and 0.010% (hereinafter referred to as "each experimental group"). The following experiments were conducted at the P&K Skin Clinical Research Center.

[0091] 4-2. Cell line selection and cell culture NHDF (Normal Human Dermal Fibroblasts) cells, a human fibroblast cell line, were provided by Lonza and cultured in FBM medium containing 0.1% INSULIN, 0.1% rhFGF-B, 0.1% GA-1000, and 2% fetal bovine serum (FBS) in a 37℃, 5% CO2 incubator, and subcultured every 2-3 days.

[0092] 4-3. Cell viability assessment The cultured NHDF cells were seeded in a 24-well plate at a concentration of 2.0×104 cells / well and cultured for 24 hours, after which the medium for each experimental group was replaced with serum-free FBM and cultured for 24 hours. After culture, 50 μl of EZ-Cytox was added per well and cultured for an additional hour. The cultured medium was transferred to a 96-well plate and the absorbance was measured at 450 nm using a VERSA max microplate reader (Molecular devices, LCC, USA). The average absorbance value for each sample group was calculated and compared with the absorbance value of Composition 1, the control group, to investigate cell viability.

[0093] As a result, as shown in FIG. 7, it was confirmed that the cosmetic composition of the present invention had no cytotoxicity compared to Composition 1, which was the control.

[0094] 4-4. Quantitative analysis of collagen production The NHDF cells were seeded in a 24-well plate at a concentration of 2.0×104 cells / well and cultured for 24 hours, after which the medium for each experimental group was replaced with serum-free FBM and cultured for 24 hours. After 24 hours of culture, the supernatant was collected and the amount of procollagen released into the medium was measured using a Procollagen Type IC-peptide (PIP) EIA Kit. The absorbance was measured at 450 nm using a VERSA max microplate reader (Molecular devices, LCC, USA).

[0095] As a result, as shown in Figure 8, the cosmetic composition of the present invention significantly increased the amount of intracellular collagen (PIP) produced in a concentration-dependent manner. Specifically, the cosmetic composition at a concentration of 0.001% to 0.010% significantly increased the amount of intracellular collagen (PIP) produced in a concentration-dependent manner to 138.52% to 166.20%.

[0096] 4-5. Measurement of fluorescence images of collagen fiber formation The NHDF cells were seeded in a 24-well plate at a concentration of 2.0 x 104 cells / well and cultured for 24 hours, then replaced with serum-free FBM containing samples diluted at each concentration and cultured for 24 hours. After 24 hours of culture, the cells were washed with HEPES-BSS and intracellular collagen fibers were stained by immunofluorescence staining. The degree of fluorescence expression was then measured using a fluorescent microscope. The results are all shown as mean ± standard deviation, and the experimental results shown are the results of three or more independent experiments, and statistical significance was verified by independent t-test at a significance level of p<0.05.

[0097] As a result, as shown in FIG. 9, it was confirmed that the degree of collagen fiber generation increased at all concentrations when the cosmetic composition of the present invention was treated.

[0098] Experimental Example 5. Confirmation of skin absorption of cosmetic composition 5-1. Selection of test subjects As shown in Table 3 below, there were no exclusion criteria, and 21 adult women aged 20 to 59 years were selected who (i) had wrinkles around the eyes, nasolabial folds, forehead wrinkles, neck wrinkles, or brow wrinkles, (ii) were fully explained to the study subjects by the study director or a person designated by the study director about the matters that should be communicated to the study subjects, and voluntarily prepared and signed a consent form, (iii) were healthy individuals without infectious skin diseases or chronic physical diseases, (iv) were available for follow-up observation during the study period, and (v) were available.

[0099] [Table 3]

[0100] The average age of the 21 test subjects was 48.762 years old, with 11 in their 40s and 10 in their 50s. In addition, the skin conditions of the 21 test subjects were 14 with dry skin, 4 with medium-dry skin, and 3 with neutral skin.

[0101] In addition, none of the test subjects answered the questionnaire regarding their experience of skin diseases, itching, pain, erythema, cosmetic side effects, drug side effects, photosensitivity, or atopic diseases, and none of the test subjects had any experience with other items.

[0102] After the explanation of the study, the subjects who agreed to participate in the study and signed the consent form were subjected to measurements as shown in Table 4 below. After using the product, a skin symptom evaluation was conducted. After the study was completed, a questionnaire survey on efficacy and preference was conducted.

[0103] [Table 4]

[0104] 5-2.Measurement method For the instrumental evaluation, the subjects were allowed to stabilise for 30 minutes in a waiting room with constant temperature and humidity conditions (20-24°C and 40-60%) to allow the skin surface temperature and humidity to adapt to the environment of the measurement space, and during this stabilisation period, water intake was restricted. For objective measurements, one researcher performed the measurements, and the same area was measured each time.

[0105] 5-3. Checking skin absorption, absorption depth, and absorption rate Skin absorption was measured using a 3D Raman Microscopy System Nanofinder® 30 (TOKYO INSTRUMENTS, Japan).

[0106] In particular, the 3D Raman system used in the test is a device that allows fine interval adjustment in the x, y, and z directions, and the z-axis focal distance can be moved in micrometer units from the skin surface to the depths of the skin. Therefore, a 3D Raman spectrum image according to depth can be obtained without damaging the test subject's skin, and the skin absorbency of cosmetics can be determined using this.

[0107] 3D Raman scanning was performed by dividing two areas, a 3x4cm2 test area and a control area, on the left forearm of the test subject, with the forearm fixed to the equipment, and measurements were taken before and 30 minutes after product use. The laser used for the measurements was 785nm, and the scanning step was fixed at 5μm. Five points were set in the x and y directions, and 11 points in the z direction, so the skin absorption of the cosmetic product can be measured up to a depth of 50μm from the skin surface. This can also be converted into absorption depth (μm) and absorption rate (μm / h).

[0108] The skin absorption was evaluated on a total of 10 levels by dividing the z-axis on the 2D image into 10 equal parts at 5 μm intervals. Therefore, the skin absorption depth could be calculated by multiplying the change in skin absorption before and 30 minutes after product use by 5 μm, and the skin absorption rate could be calculated by dividing the absorption depth by 0.5 hours, which was the duration of use.

[0109] As shown in Table 5, FIG. 10 and FIG. 11, the skin absorption was statistically significantly improved after 30 minutes of using the composition 3 of the present invention compared to before use.

[0110] In addition, it was confirmed that composition 3 was 1.871 times and 187% more effective than composition 1, which was a control group containing spicules without diamond coating, and a statistically significant difference was observed even 30 minutes after use. These results indicate that the diamond-coated cosmetic composition of the present invention has a more pronounced skin absorption effect than the non-coated control group.

[0111] [Table 5]

[0112] As shown in Table 6, Figures 12 and 13, the skin absorption depth was 1.791 times and 179% deeper when Composition 3 of the present invention was used compared to the control group before and after use. This result indicates that the diamond-coated cosmetic composition of the present invention is absorbed deeper into the skin than the non-coated control group, and has a significant effect.

[0113] [Table 6]

[0114] As shown in Table 7, Figures 14 and 15, the skin absorption rate was 1.971 times and 179% faster when using composition 3 of the present invention compared to the control group before and after use. This result means that the diamond-coated cosmetic composition of the present invention is absorbed into the skin faster than the non-coated control group, and has a significant effect.

[0115] [Table 7]

[0116] 5-4.Efficacy questionnaire survey After using the test product, the test subjects answered the questionnaire directly on a five-point scale for each measurement item: very good (4), good (3), average (2), bad (1), and very bad (0). Researchers calculated the percentage of test subjects who answered each question to determine whether the test product was effective.

[0117] As shown in Table 8 below, it was confirmed that the cosmetic composition of the present invention has a high effect of improving physical sensation.

[0118] [Table 8]

[0119] 5-5. Product preference questionnaire survey evaluation After using the test product, the test subjects answered a questionnaire directly about their impressions of the product. The evaluation items were skin moisturization, skin smoothness, application ease, fragrance, and overall impression of the product, and they were asked to rate them on a five-point scale: very good (4), good (3), average (2), bad (1), and very bad (0).

[0120] As shown in Table 9 below, it was confirmed that the test subjects had a high preference for the cosmetic composition of the present invention.

[0121] [Table 9]

[0122] 5-6. Safety assessment and abnormal reaction assessment The safety of the test product was evaluated by calculating the incidence rate of abnormal reactions by combining all abnormal reactions confirmed in all test subjects who used the test product and all abnormal reactions reported during the test period, and this was used as the data for evaluating the safety of the product. In addition, for abnormal skin symptoms that occurred during the test product use, a questionnaire survey was conducted during the test period to confirm the occurrence and severity of symptoms. As a result, the evaluation was conducted by combining the results of the researchers' visual evaluation of the test product application sites and the results of the questionnaire surveys of the test subjects. A stability evaluation and an abnormal reaction evaluation were conducted.

[0123] During the test period, the researchers visually evaluated the test areas and found no particular abnormal skin reactions.In addition, a questionnaire survey of the test subjects revealed no particular reports of abnormal skin reactions, and no test subjects experienced any abnormal reactions during the test period.

[0124] Although the embodiments have been described above with reference to limited examples and drawings, those skilled in the art may make various modifications and variations from the above description, for example, the techniques described may be performed in a different order than described, and / or the components described may be combined or combined in a different manner than described, or may be replaced or substituted by other components or equivalents, and still achieve suitable results.

[0125] Accordingly, other implementations, other embodiments, and equivalents of the claims are intended to be within the scope of the following claims.

Claims

1. (a) cleaning the spicules; (b) encapsulating a first active ingredient within the inner pores of the washed spicules; (c) coating the exterior of the spicules having the first active ingredient encapsulated in the inner pores with silica; (d) reacting the silica-coated spicules with aminosilane and lysine to coat them with amino groups; and (e) coating the amino-coated silica with a second active ingredient and diamond; Including, The first active ingredient and the second active ingredient are each at least one selected from the group consisting of collagen, amino acids, tripeptides, tetrapeptides, and water-soluble vitamins; The first and second active ingredients may be the same or different. A method for producing spicules coated with diamonds and ingredients effective for improving skin.

2. The method for producing spicules according to claim 1 , wherein the collagen is one or more selected from the group consisting of fish collagen, nano-collagen, low molecular weight collagen, plant collagen, and collagen peptides.

3. The method for producing a spicule according to claim 1, wherein the aminosilane in step (d) is 3-aminopropyltrimethoxysilane.

4. The method for producing spicules according to claim 1, wherein the lysine in step (d) is poly-L-lysine.

5. The method for producing spicules according to claim 1 , wherein the mixing ratio of aminosilane and lysine in step (d) is 1:1 to 500:

1.

6. The method for producing spicules according to claim 1 , wherein the diamond in step (e) is one or more selected from the group consisting of microdiamonds, nanodiamonds, and colloidal diamonds.

Citation Information

Patent Citations

  • Cosmetic

    JP1994107520A

  • Cosmetic composition containing porifera spicule coated with sawhangsan and method for manufacturing the same

    KR101851742B1

  • A structure for accelerating transdermal absorption, a manufacturing method the same, and a cosmetics composition comprising the same

    KR102074214B1

  • Color cosmetic composition comprising color base and extract reacted with enzyme of low temperature and high pressure

    KR102242215B1

  • Coated sponges

    WO2021206784A1